Gestión de activos intangibles psicosociales en el sector financiero cubano 2024: un enfoque estratégico basado en un modelo conceptual - Montané Marsal, Naivi (2025)
Psychosocial intangible assets (PIAs), such as leadership, commitment, job satisfaction, work competencies, and perceived outlook, have demonstrated their potential to generate organizational value. This study aimed to develop a conceptual model for the management of PIAs, and conducted a descriptive cross-sectional analysis in 2024 at the Central Bank of Cuba. The sample, selected through purposive sampling, consisted of the institution’s employees. Research techniques included a questionnaire, an expert panel (Delphi method), and the Analytic Hierarchy Process (AHP). Also, assessed the reliability of the questionnaire using Cronbach’s alpha coefficient. Indices of weight, importance, consistency, and strategic alignment were calculated. The results show a favorable correspondence between institutional strategies and organizational performance. The analysis revealed moderate to strong positive correlations, particularly among perceived outlook, job satisfaction, leadership, and commitment. Finally, lowest, though still positive, correlation occurred between perceived outlook and work competencies. The model supports continuous improvement in institutional management.